INITIAL CREATIVEPRENEUR THROUGH CREATIVITY BASED COMMUNITY SERVICES - Dewanti, Paula; Permana, Putu Adi Guna (IKRA-ITH ABDIMAS, 2018)
ABSTRACTKnown for its distinctive art, Bali declared as one of the main tourist destinations of Indonesia. Painting isone of them, in addition to carving, dance and many other arts. Besides canvas as a medium of painting,Balinese artists also use other media to express their artwork. In this Community Service, the author highlightedartisans of wooden egg painting, located in Banjar Gerih, Batuan Village, District Sukawati, Gianyar, Bali,Indonesia. Gianyar Regency, itself, well-known as the centre of art. Based on the problems encountered, the useof online media, were taken as an alternative solution to streamline marketing as well as increase number ofproduct sales. Performance indicator is a 100% increase in partner revenue; creating an online marketingaccounts at one of online marketplace and able to maintain the account.